The Location of the Distribution Center Using the Hierarchical Analysis of the Decision-Making Problem: The Analytic Hierarchy Process (AHP) - Oliwia ŚLUSARCZYK (Communications of International Proceedings, 2021)
Currently, one of the main tasks of supply chain management is the effective design of distribution networks. In particular, the identification of good locations for distribution centers through simulations taking into account geographical location of customers, road network, time constraints and capacity is always difficult. Distribution centers are the units constituting the basis for solving problems in the logistics industry. The planning of distribution centers is a complex task since it is not a separated segment of the system but rather a part of a very complex network so that the methods of designing logistics and distribution centers are also subject to constant research and improvement. In order to plan the location of distribution centers many methods of the multi-criteria decision support are used. The objective of the article is an attempt to use the Analytic Hierarchy Process (AHP) analysis to locate the distribution center.
Keywords: Distribution center; distribution center location; AHP